(untitled) (Swiss Medical Weekly, 2023)
In recent years, patient narratives have attracted increasing attention as a valuable source of insights into the subjective experience of healthcare. This paper outlines a best-practice approach to the collection, analysis, and use of patient narratives, based on current literature and on the experience of developing the Swiss Database of Individual Patient Experiences (DIPEx). The DIPEx project aims to provide a systematic and methodologically rigorous collection of patient narratives on various health situations and topics. This paper presents and details the DIPEx approach as a current standard in the field, offering a comprehensive overview and discussing the potential uses and benefits of patient narratives: improve healthcare practice, empower patients and caregivers, help structure better communication in healthcare, and contribute to medical teaching and learning.